Studies in magnetoelasticity - Ryburn, F (2024)
This thesis is divided into two halves: the first reports on the study of surface acoustic waves (SAWs) in thin magnetic films and their magnetoelastic coupling with spin waves; the second describes a study of magnetoelastic torque sensors used in electric bicycles.